Image Processing Based Fault Detection Approach for Rail Surface - Yaman, Orhan; Karakose, Mehmet; Akin, Erhan; Aydin, Ilhan (Ieee, 2015)
Railway transport is getting more and more preferred mode of transportation. Railway line should be established in a robust manner because of construction of used heavy vehicles. A small fault, which occurs in the railway line, can lead to serious accidents. Therefore, the railway line should be controlled at certain time intervals. Faults detected during the control process should be repaired and the required maintenance should be performed. In this study, an image processing based method has been proposed to detect the defects of rail surface. In the proposed method, the images were taken from two cameras, which of them were placed at different angles on the experimental setup. The preprocessing stage was made by applying OTSU method to obtained images. The rail surface is determined by using Canny edge detection and Hough transform. Faults occurred on the rail surface were detected by combining images taken from two camera. The accuracy of the proposed method was increased by using the images taken from two different cameras.
Ray Yüzeyi için Görüntü Işleme Tabanli Ariza Tespit Yaklaşimi
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: rail surface detection; rail surface faults; image processing; railway